The first clinical data of the SAPIEN 3 aortic valve in the treatment of aortic stenosis in China - Shang, Xiaoke; Pan, Xiangbin; Zhang, Gejun; Jiang, Zhengming; Liu, Xianbao; Song, Guangyuan; Li, Yi; Wang, Yan; Luo, Jianfang; Tang, Yida; Yuan, Yiqiang; Wu, Yongjian; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Data on outcomes following transcatheter aortic valve replacement with SAPIEN 3 in China is limited as it was approved by the National Medical Products since 2020. The present study was designed to collect clinical data on the SAPIEN 3 aortic valve in Chinese patients with bicuspid aortic valve and tricuspid aortic valve stenosis. Methods: We analyzed the patient characteristics, procedural features and procedural outcomes of the first 438 patients (223 for bicuspid aortic valve and 215 tricuspid aortic valve) from 21 provinces in 74 sites treated with the SAPIEN 3 valve system for transcatheter aortic valve replacement between September 2020 and May 2022. Results: Procedural mortality was 0.7%. 5 cases during the operation were converted to surgery. Among 438 cases, permanent pacemaker implantation was performed in a total of 12 cases (2.7%). The patient had severe leaflet calcification of the aortic valve, with moderate and severe calcification reaching 39.7% and 35.2% respectively. The size of the implanted valves was predominantly 26mm and 23mm, reaching 42.5% and 39.5% respectively. The incidence of moderate or severe perivalvular leak in the postoperative period was 0.5%, with a predominance of 90/10 and 80/20 valve deployment height. There was a significant difference in the deployment height of the valve between bicuspid aortic valve and tricuspid aortic valve, with the bicuspid aortic valve having a more deployment height of 90/10. Annulus size in bicuspid aortic valve group was significantly larger than tricuspid aortic valve group. Valve sizing for oversized, within size, and undersized were different between bicuspid aortic valve and tricuspid aortic valve. Conclusions: Procedural success rates were high, with similar and good results for bicuspid aortic valve and tricuspid aortic valve, low perivalvular leak for both valve types, and low permanent pacemaker implantation rates for both valve types. Annulus size, valve sizing and coronary artery height were significantly different in the BAV and TAV group.